Performance of commercial scale removers in removing calcium carbonate (CaCO3) rich scales - Munira, Abdul Aziz (2011)
The presence of high concentration metal ions such as Ca 2+ and Mg 2 together with carbonate and sulphate 'ions in industrial process always gave rise to scaling. The carbonate, and sulfate of calcium, strontium and barium are the most common scales formed. Scales are usually formed when salt water is saturated with the ions and exposed to drastic changes in temperature and pressures. The composition and forms of scales may vary dependent on industry such as the formation of calcium phosphate in sugar refineries while calcium carbonate scaling in boiler tube of steam generating facilities. The objectives of this research are to characterize the nature and component of CaCO 3 based scales, to establish the ability of commercial scale remover formulation in removing CaCO 3 scales and to study the impact of these commercial scale removers on pipe material. Sample of scale were collected at selected plant. The scale samples were analyzed using FourierTransform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) technique and Thermal Gravimetric analysis. FTIR analysis confirmed the dominance of carbonate phase in the samples while the XRD analyses confirmed the presence of CaCO 3 as calcite and aragonite. Thermal Gravimefric Analysis enables the determination of amount of carbonate present in the samples. The efficiencies of different commercial scale remover were compared based on their ability to dissolve the scale sample. The effects of scale remover towards carbon steel sample that are commonly used as pipe material were studied. Formulation AM1082 was found to be the most efficient in dissolving the scale sample followed by formulation AM1081, AJvI1O8O, sulfamic acid and last the sulfuric acid. Formulation AM1082 has been found to cause minimal leaching of the piped material while sulfuric acid caused the worst effect. Overall AM1 082 scale remover proved to be the best formulation and less harmful to the pipe material.